Overweight Among Medical Students in Universal College of Medical Sciences: A Descriptive Cross Sectional Study - Gurung, Preetu; Tiwari, Indu; Joshi, Bishal; Kar, Sanjit Kumar (Journal of Universal College of Medical Sciences, 2023)
INTRODUCTION Overweight is a lifestyle disorder affecting both physical and psychological health of a person. The rate of overweight index is rising in people from all walks of life. The main aim of this study is to ﬁnd out the prevalence of overweight among medical students in a tertiary care center creating self-awareness in them. MATERIAL AND METHODS This is a descriptive cross-sectional study done in 385 students in a tertiary care hospital from 15th August 2022 to 30th Novem- ber 2022.The sample was collected by simple random sampling method after the approval from the Institutional Review Committee of Universal College of Medical Sciences (reference number UCMS/IRC/100/22). Height in meter and weight in kilogram of students were measured to calculate body mass index and grouped according to Asian Criteria categories normal BMI is between 18.5 to 22.9 kg/m2, BMI 23 to 24.9 kg/m2 would be considered as overweight and BMI > 25 kg/m2 would be considered as obese. Data was analyzed by using Statistical Package of Social Science software version 16. RESULTS Among 385 students, 70 (18.1%) were found to be overweight with 95% Conﬁdence Interval. Overweight males were 37 (9.6%) and females were 33 (8.5%) respectively out of the total number of male 173 (44.93%) and female 212 (55.07%). The mean age of the students and the mean BMI was found to be 21.01 ± 2.01 and 22.39 ± 3.54 respectively. CONCLUSION The current study shows the prevalence of overweight among medical students is slightly higher than in studies done in similar settings.